Effect of the Pronated Pull-Up Grip Width on Performance and Power-Force-Velocity Profile. Issue 4 (2nd October 2021) - Ortega-Rodríguez, R.; Feriche, B.; Almeida, F.; Bonitch-Góngora, J.; Padial, P.
ABSTRACT: Purpose : The objective of this study was to investigate the influence of the grip width on the power-force-velocity-profile, the maximal strength, and performance during a repetition to failure test in the pull-up exercise (PU). Method : Fourteen trained males performed an incremental loading and repetitions to failure test with the PU exercise using biacromial and free grip widths. Power-force-velocity relationship, 1RM, and repetitions completed were determined. Results : The mean grip width used by participants was 20.04% higher in the free grip width condition ( p < .001). There were similar results in the 1RM ( p = .954), repetitions to failure test ( p = .117), and power-force-velocity profile ( p > .05) in both grip width conditions. A stronger relationship was observed between 1RM and repetitions to failure test during the biacromial ( R 2 = 0.720; p < .001) with respect to the free grip width ( R 2 = 0.607; p = .002). Conclusion : Therefore, the choice of a free or a biacromial grip width does not affect the maximal strength, power-force-velocity relationship, nor the repetitions to failure during the PU exercise.